Promoting coping competence for psychological stressors in nursing training : a controlled pedagogical intervention - Warwas, Julia [Verfasser]; Krebs, Philine [Verfasser]; Vorpahl, Wiebke [Verfasser]; Weyland, Ulrike [Verfasser]; Wilczek, Larissa [Verfasser]; Seeber, Susan [Verfasser]; Wittmann, Eveline [Verfasser] (My University, 2024)
„Background: Multiple stressors as well as health-and quality-impairing effects of strain in the nursing profession require the systematic acquisition of competence in dealing with these demands, starting at the stage of initial vocational training. This study investigates whether an instructional design, which merges didactic principles of nursing education with concepts and training measures from stress psychology, promotes the acquisition of stress coping competence more effectively than regular teaching on the relevant curricular field at nursing schools. Methods: The quasi-experimental study design, based on the Solomon four-group plan, included 332 trainees in Germany. The assessment of stress coping competence at the beginning and at the end of the intervention provided a video-stimulated situational judgment test covering nursing-specific stressful situations. All were validated by field experts. Complementing group comparisons, regression analyses examined intervention effects at the individual level while controlling for other predictors of learning success. Results: The highest solution rates for the two basic dimensions of stress coping competence, i.e., (1) situation assessment and (2) strategy selection and justification, occurred in the treatment classes without a pretest. At the individual level, treatment effects were confirmed for the first dimension. Students with a migration background showed lower competence gains than other students. Conclusion: The instructional design and the competence test provide valuable foundations for promoting and for diagnosing coping skills. Nevertheless, subsequent studies should examine adaptive support for different learner groups. Furthermore, additional observational phases should focus on the deliberate practice of acquired coping strategies in the practical training settings of nursing education.“ (authors' abstract; BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; P 2.3 Auszubildende; 370; 610; Pflegeberuf; Berufsausbildung; Auszubildender; Psychische Faktoren; Stress; Stressbewältigung; Resilienz; Kompetenzentwicklung